1996
DOI: 10.1073/pnas.93.24.13979
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the sequence of an immunoglobulin V-gene alters the resulting pattern of hypermutation

Abstract: following correction should be noted. On page 2475, the second line of the left column that reads ". . . were reconstituted with aly͞aly BM cells after lethal irradiation" should read ". . . were reconstituted with aly͞ϩ BM cells after lethal irradiation."Immunology. In the article "Modifying the sequence of an immunoglobulin V-gene alters the resulting pattern of hypermutation," by Beatriz Goyenechea and César Milstein, which appeared in number 24, November 26, 1996, of Proc. Natl. Acad. Sci. USA (93, 13979-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…71,72 Generally, the nature of somatic mutations in hypermutating B cells indicates a preference for transitions over transversions with purines being preferentially targeted over pyrimidines, suggesting strand bias; mutations are concentrated mainly in CDRs and most often are single nucleotide substitutions. [72][73][74][75][76] However, investigators have reported deletions or insertions of base stretches of varying length in hypermutating B cells and have concluded that this is a byproduct of the somatic hypermutation machinery within the GC rather than a result of V(D)J recombination in earlier stages of B cell ontogeny. 77,78 Furthermore, it appears that several types of oncogene translocations and Ig HC/LC trancations in heavy chain disease and AL amyloidosis are the result of this phenomenon.…”
Section: Antigen Selection Imprint On MM Ig Genesmentioning
confidence: 99%
“…71,72 Generally, the nature of somatic mutations in hypermutating B cells indicates a preference for transitions over transversions with purines being preferentially targeted over pyrimidines, suggesting strand bias; mutations are concentrated mainly in CDRs and most often are single nucleotide substitutions. [72][73][74][75][76] However, investigators have reported deletions or insertions of base stretches of varying length in hypermutating B cells and have concluded that this is a byproduct of the somatic hypermutation machinery within the GC rather than a result of V(D)J recombination in earlier stages of B cell ontogeny. 77,78 Furthermore, it appears that several types of oncogene translocations and Ig HC/LC trancations in heavy chain disease and AL amyloidosis are the result of this phenomenon.…”
Section: Antigen Selection Imprint On MM Ig Genesmentioning
confidence: 99%
“…However, there is an interesting difference. In vivo, there are two mutational hot spots that revolve around the consensus motif GAGCT or TA when read in the coding strand (9)(10)(11). There is evidence that in vivo mutations occur in both strands and, therefore, the complementary sequences of those motifs are also (albeit to a lesser extent) mutational hot spots (12,13).…”
mentioning
confidence: 99%
“…Studies have shown that AID preferentially mutates a position at or around hotspot motifs,73, 74, 75 which are more frequently observed in the CDR regions than the framework regions 74, 76, 77. Moreover, targeted nucleotide positions have increased chances to generate transition mutations (A↔G, C↔T), which are generated more frequently than transversion mutations, such as A↔C, A↔T, C↔G, or G↔T 74.…”
Section: Antibodyomics6mentioning
confidence: 99%